1984
DOI: 10.1111/j.1365-2761.1984.tb01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative kidney disease of salmonid fish: a review

Abstract: A detailed review of proliferative kidney disease (PKD) in salmonids is presented. The introduction places the disease in a historical context. The various aspects of the disease are described from the existing literature, together with latest findings from current research. Particular emphasis is given to epidemiology, aetiology and pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…In susceptible rainbow trout infected with a presumably non-pathogenic strain of C. shasta , parasites were identified in the presence of increased mucosal IgT antibody [24]. Although it is not known if this response is protective against C. shasta , protective antibody responses have been demonstrated in fish surviving other myxozoan infections [40, 41, 42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…In susceptible rainbow trout infected with a presumably non-pathogenic strain of C. shasta , parasites were identified in the presence of increased mucosal IgT antibody [24]. Although it is not known if this response is protective against C. shasta , protective antibody responses have been demonstrated in fish surviving other myxozoan infections [40, 41, 42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…The fish were fed daily and monitored for possible health impairment over 8 weeks. They were then killed by immersion in an 1/2500 aqueous solution of 2‐phenoxyethanol (Prolabo, Paris, France) and examined for PKD infection on the basis of nephromegaly scored according to Clifton‐Hadley et al . (1984) and splenomegaly, and for the presence of parasitic cells in kidney tissue imprints stained with May–Grünwald Giemsa, microscopically observed at ×200.…”
Section: Methodsmentioning
confidence: 99%
“…In salmonids, the myxozoan Ceratomyxa shasta Noble, 1950 was found to infect fish between April and December (Hendrickson, Carleton and Manzer, 1989) and the related intestinal disease, ceratomyxosis, generally occurs at water temperatures above 10 xC (Palenzuela and Bartholomew, 2002). Similarly, the massive proliferation of extrasporogonic stages of Tetracapsuloides bryosalmonae Canning et al 2002, the cause of proliferative kidney disease (PKD) in salmonids, occurs only above 9 xC (Ferguson, 1981 ;Clifton-Hadley, Bucke and Richards, 1984). It has been suggested that the impact of temperature on the development of PKD primarily influences the kinetics of Tetracapsuloides multiplication in the host (Gay, Okamura and De Kinkelin, 2001) and similar conditions might apply for other myxozoan species in temperate climates.…”
Section: Introductionmentioning
confidence: 99%